Medicine advertisements: evaluation and implementation of cema-community method - Chairun Wiedyaningsih; Nia Primayani; Warastuti . (Indonesian Journal of Pharmacy, 2011)
Non-prescription medicines are advertised widely to general public. These advertisements attempt to influence consumers’ choices about medicines. Since the  advertisements  rare  to  give  objective  information,  therefore  it  may  affect people’s perception and have potential harmful effect for public health. In order to  improve  the  use  of  medicines  by  general  public,  the  CEMA-community (Critical  Evaluation  Medicine  Advertisement  by  the  community))  was  proven effective  empower  community  in  evaluating  medicine  advertisements.  The objectives of the study, therefore, were to investigate medicine advertisements, and improve knowledge and skills of participants in critically evaluating medicine advertisements.  Medicine  advertisements  running  within  the  period  of  study were  evaluated  and  analyzed  according  to  the  Indonesian  legal  requirements. Community  empowerment  to  improve  participants’  knowledge  and  skills  was conducted  using  CEMA-community  method.  The  method  consisted  of  two activites,  the  first  was  a  brief  lecture  and  the  second  was  small  group discussions in a problem-oriented approach. Data on knowledge was obtained by questionnaire.  Data  on  skills  was  assessed  by  the  number  of  inappropriate claims they could identify the advertisements. All data was collected at baseline, immediately,  and  one  month  after  intervention.  Medicine  advertisements  in television media accounted for 15% off all commercials, with 21.53%; 17.98%; 14.17%;  and  10.08%  being  medicine  products  for  influenza, analgesic/antipyretic,  supplement,  and  cough,  respectively.  Incomplete  and misleading  information  mostly  appeared  in  the  advertisements.  Intervention study  showed  that  the  average  of  participants’  knowledge  in  subtopic  of medicine  misleading  was  low  and  could  be  increased  from  34.2  (pretest)  with maximum score 100, to 65.3 (post I) and 58.3 (post II). Participants’ skills also improved  immediately  after  intervention  and  this  was maintained  at  the  one month  follow  up  (score  means:  3.33;  26.67;  26.67 of  maximum  score  100,  at pre test, post I, and post II, respectively).Key  words:  medicine  advertisements,  community  empowerment,  CEMA-community method, knowledge; skills